Volatile Metabolomics with Focus on Fungal and Plant Applications - A Review - She, Jinyan; Mlsna, Deb A.; Baird, Richard E.; Mohottige, Chathuri U.G.; Mlsna, Todd E. (Current Metabolomics, 2018)
The establishment of metabolomics has benefited from recent developments in analytical platforms and bioinformatics, which allow for comprehensive analysis of volatile metabolites in a biosystem. Consequently, metabolomics has become one of the most dynamic of all the omics over the last decade. Mass spectrometry based metabolomics of fungal and plant volatile metabolites has been a recent focus of intense study. Volatile metabolites are important information carriers providing insight into the health of organisms throughout their lifecycle while elucidating the physiological effects of varied environmental perturbations and disease pathogenesis. Here, we review recent literature including methods and applications of metabolomics analysis. We begin with an introduction of metabolomics, then focus on identification and quantification of the volatile metabolites produced from fungus and plants. Detailed discussion on sampling methods, pre-treatment of gas chromatography/mass spectrometry data, and chemometric analysis of volatile compounds follow. The review also provides examples of volatile metabolomic applications in a number of research fields. The aim of this review is to provide a basic understanding of and an outline of the required workflow for a metabolomics study of the volatile organic compounds produced by plants and fungi.
Keywords: Metabolomics